KABUPATEN/KOTA DI PROVINSI ACEH - Fajri Hadi, Abubakar Hamzah, Mohd. Nur Syechalad. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2014)
Abstract: Inequality is a development problem that cannot be eliminated, especially in developing countries.This study was to analyze the growth economic and inequalities between districts or cities in Aceh province. To see this inequality Aceh GDP data was used to the model Williamson Index.The results showed that the rate coefficient of inequality of growth economic in the province of Aceh has improved. This is indicated by the high coefficient of inequality from 2000 to 2012. Government spending and the number of people positive and significant effect in increasing the index of inequality across districts or city cities in Aceh province. 51.09 percent of the variation of the index of income inequality can be explained by government spending and population, while the remaining 48.91 percent is explained by other factors outside the model. Williamson index analysis results showed in the district or city having a very high inequality in 2000 and continues to grow so that in the year 2012 fell limp below average although still at the level of inequality of growth with a high index, but were able to show better development, for example Aceh Barat Daya district in 2001 had a very high inequality with coeficien index at 0,862 and further declined in 2012 with the index of inequality for 0,761 coeficien index(IW) is below the average. To reduce the level of inequality between regions in the province of Aceh in the future, the Government of Aceh need to increase spending on capital expenditures for the Central Region and the South West and the creation of employment for encourage the growth of regional economic. Keywords: development economic, inequality, government expenditure. Abstrak: Ketimpangan merupakan masalah pembangunan yang belum dapat dihapuskan terutama pada negara sedang berkembang. Penelitian ini bertujuan untuk menganalisis pembangunan ekonomi dan ketimpangannya di Provinsi Aceh. Untuk melihat pembangunan dan ketimpangan ini digunakan data PDRB Aceh dengan menggunakan model Indeks Williamson dan Tipologi Klassen. Hasil penelitian menunjukkan bahwa angka koefisien ketimpangan pembangunan ekonomi di Provinsi Aceh berfluktuasi dan koefisiennya masih tinggi. Hal ini ditunjukkan oleh tingginya koefisien ketimpangan pendapatan perkapita dari tahun 2000 sampai dengan 2012. Pengeluaran pemerintahdan jumlah penduduk berpengaruh positif dan signifikan dalam meningkatkan indek ketimpangan pertumbuhan ekonomi Kabupaten/Kota di Provinsi Aceh. 51,09 persen variasi dari indek ketimpangan pendapatan dapat diterangkan oleh pengeluaran pemerintah dan jumlah penduduk, sedangkan 48,91 persen lagi dapat dijelaskan oleh faktor-faktor lain di luar model ini. Hasil analisis indeks williamson menunjukkan di Kabupaten/kota mengalami ketimpangan yang sangat tinggi pada tahun 2000 dan terus tumbuh sehingga pada tahun 2012 ketimpangannya turun dibawah rata-rata meskipun masih berada di tingkat yang tinggi namun mampu menunjukkan pembangunan yang lebih baik, misalnya Kabupaten Aceh Barat Daya pada tahun 2000 mengalami ketimpangan yang sangat tinggi dengan koefisien ketimpangan 0,862 dan selanjutnya menurun pada tahun 2012 dengan indeks ketimpangan (IW) dibawah rata-rata dengan koefisien ketimpangan 0,761. Untuk mengurangi tingkat ketimpangan antar wilayah di Provinsi Aceh di masa yang akan datang, pemerintah Aceh perlu meningkatkan pengeluarannya untuk kabupaten yang berada di wilayah Tengah dan Barat Selatan dan penciptaan lapangan kerja untuk mendorong pembangunan ekonomi didaerah ini. Kata kunci : Pembangunan ekonomi, ketimpangan, pengeluaran pemerintah.